2023
DOI: 10.3390/ijms24043199
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Amino Acid Profiles of Proneural and Mesenchymal Brain-Tumor Initiating Cells

Abstract: Glioblastomas are highly malignant brain tumors that derive from brain-tumor-initiating cells (BTICs) and can be subdivided into several molecular subtypes. Metformin is an antidiabetic drug currently under investigation as a potential antineoplastic agent. The effects of metformin on glucose metabolism have been extensively studied, but there are only few data on amino acid metabolism. We investigated the basic amino acid profiles of proneural and mesenchymal BTICs to explore a potential distinct utilization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 58 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…Adeberg et al observed longer progression-free survival among diabetic patients with primary GBM who received metformin treatment [ 59 , 61 ]. Similarly, Seliger et al demonstrated improved overall and progression-free survival in patients with high-grade gliomas, particularly WHO grade III tumors, under metformin therapy [ 62 ]. Notably, this association was more pronounced in grade III gliomas compared to grade IV tumors.…”
Section: Metformin For High-grade Glioblastoma+trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adeberg et al observed longer progression-free survival among diabetic patients with primary GBM who received metformin treatment [ 59 , 61 ]. Similarly, Seliger et al demonstrated improved overall and progression-free survival in patients with high-grade gliomas, particularly WHO grade III tumors, under metformin therapy [ 62 ]. Notably, this association was more pronounced in grade III gliomas compared to grade IV tumors.…”
Section: Metformin For High-grade Glioblastoma+trialsmentioning
confidence: 99%
“…In a 2019 retrospective report, Seliger et al suggested a potential correlation between metformin treatment and better survival outcomes in patients with grade III gliomas, possibly linked to a higher percentage of IDH mutations in WHO grade III gliomas [ 62 ]. Further analysis by Seliger et al involving a larger cohort of GBM patients failed to establish a significant relationship between metformin monotherapy and overall survival or progression-free survival, underscoring the complexity of the relationship between metformin use and glioma prognosis [ 62 , 63 ].…”
Section: Metformin For High-grade Glioblastoma+trialsmentioning
confidence: 99%